Peningkatan Pemahaman Konsep Akar dan Perpangkatan dengan Model Pembelajaran Take and Give di Kelas V SDN Bendogerit 2 Kota Blitar - Lina Krisnawati (LP. Ma'arif Janggan Magetan, 2021)
Mathematics learning basically has abstract characteristics, as well as tiered concepts and principles. This causes many students to find it difficult to learn mathematics. The success of learning mathematics in elementary schools is shown by the mastery of the material by students. Mathematics students about roots and powers in class V SDN Bendogerit 2 Blitar City can be seen that they have not yet achieved the expected completeness. The results obtained in learning from 20 students who achieved completeness were only 5 students or 25%. With these results, the researchers conducted qualitative research on mathematics learning. The type of research conducted is Classroom Action (CAR), with data analysis techniques used are data reduction, data presentation, and drawing conclusions. The learning model used is Take and Give, which is a learning model that has a learning syntax using media cards that contain student names, study materials, and given names, inform competencies, presentation materials.